Synthesis and Characterization of Adsorbent Magnetic Kaolin - Nelly Wahyuni; Harlia Harlia (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2025)
Kaolin as an adsorbent has difficulties separating it from the adsorbate solution because it requires centrifugation and precipitation methods, which require significant costs, time, and energy. Modification of kaolin with magnetite was carried out to increase the effectiveness of adsorption from the paracetamol solution. Kaolin-magnetite (KM) adsorbent was made by combining activated kaolin and Fe(III)/Fe(II) solution with a mole ratio of 2:1 using the coprecipitation method. The resulting activated kaolin, magnetite, and kaolin-magnetite were characterized using X-ray Fluorescence (XRF), X-ray Diffractometer (XRD), Fourier Transform Infrared (FTIR), Gas Sorption Analyzer (GSA), and Vibrating Sample Magnetometer (VSM). The presence of magnetite makes it easier to separate KM from the paracetamol solution, with 97.17% of KM being taken by the magnetic rod.